Teaching Students to Think Creatively (in Drawing Classes) - Odiljanovna, Yakubova Nafisa (Indonesian Journal Publisher, 2024)
In the first way of developing spatial imagination, the spatial imagination of students is increased by using drawings given on objects, mentally dividing them into simple figures and drawing up their clear image. Indeed, if there is a clear image of the object depicted in the figure, it becomes easier for the student to visualize the object, the appearance of which is given in the figures. Through a qualitative analysis of teaching methodologies and student experiences, this research investigates the strategies employed by art instructors to stimulate creative thinking in drawing classes. It explores how instructors design curriculum, structure assignments, and provide feedback to encourage students to approach drawing with imagination and inventiveness. Furthermore, this study examines the impact of these teaching practices on students' creative development and artistic growth. By analyzing student artworks, reflections, and assessments, it evaluates the effectiveness of different pedagogical approaches in nurturing creative thinking skills. The findings of this research shed light on the importance of teaching students to think creatively in drawing classes and offer practical insights for art educators seeking to enhance their teaching practices. By fostering a supportive and stimulating learning environment that encourages experimentation and risk-taking, instructors can empower students to unlock their creative potential and develop as artists. This research contributes to our understanding of the role of creativity in art education and provides valuable guidance for educators striving to cultivate creative thinking skills in their students within the context of drawing classes.